Species delimitation of southeast pacific angel sharks (Squatina spp.) reveals hidden diversity through dna barcoding - Cañedo-Apolaya R.M. (2021)
Angel sharks are distributed worldwide in tropical to subtropical waters. Across the Eastern Pacific Ocean (EPO), two valid species are reported: The Pacific angelshark Squatina californica and the Chilean angelshark Squatina armata; however, there is still uncertainty about their geographic distribution, mainly along the northern Peru coast where the species have been reported to be sympatric. The aim of this study is to describe the genetic differences between the genus Squatina from the EPO, including samples from northern Peru, and using DNA barcoding and three species delimitation models: Poisson tree processes (PTP) model, Bayesian implementation of the PTP (bPTP) model and the general mixed Yule coalescent (GMYC) model. The three approaches summarized 19 nominal Squatina species in 23 consensus Molecular Taxonomic Units (MOTU). Only 16 of them were in accordance with taxonomic identifications. From the EPO, four Squatina MOTUs were identified, one from North America (S. californica USA/Mexico) and three sampled in northern Peru, S. californica Peru, S. armata and Squatina sp. (a potential new species). This study contributes to the management and conservation policies of angel sharks in Peru, suggesting the presence of an undescribed species inhabiting the northern Peruvian coast. The use of molecular approaches, such as DNA barcoding, has the potential to quickly flag undescribed species in poorly studied regions, including the Southeast Pacific, within groups of ecologically and economically important groups like angel sharks. © 2021 by the authors. Licensee MDPI, Basel, Switzerland.